UPAYA GURU MENINGKATKAN MINAT MEMBACASISWA PADA PEMBELAJARAN BAHASA INDONESIA KELAS IIIDI UPTD SD NEGERI DULOLONG KECAMATANALOR BARAT LAUT KABUPATEN ALOR - Lutfia Tika; Ismail Tamal Biat; Mahmud Abdullah Noho (Jurnal Edukasi, 2026)
Abstract: Lutfia Tika Dewi Ahmad. "Teachers’ Efforts to Increase Students’ Reading Interest in Indonesian Language Learning for Grade III at UPTD SD Negeri Dulolong, Alor Barat Laut District, Alor Regency." This study aims (1) to investigate the efforts made by the classroom teacher to increase reading interest in Indonesian language learning for Grade III students at SD Negeri Dulolong, and (2) to identify the factors influencing students’ reading interest in the subject. This research employed a descriptive method with a field study design. The research questions were: (1) How does the classroom teacher enhance reading interest in Indonesian language learning for Grade III students at SD Negeri Dulolong? (2) What factors influence students’ reading interest in this learning context? The researcher acted as the key instrument, with data collected through triangulation techniques, including observation, interviews, and documentation. The subjects were the classroom teacher and Grade III students, with the study conducted over two months, from December 2024 to January 2025. Primary data were obtained directly from the teacher and students, while secondary data consisted of official documents, books, and reports. Using a qualitative approach, the study found that the teacher implemented various strategies to foster reading interest, such as creating an attractive reading corner in the classroom, fostering an enjoyable learning atmosphere, employing engaging media and teaching methods, and encouraging students to read before lessons. Parental involvement and the availability of relevant reading materials also played a supporting role. These efforts contributed to an increase in students’ reading interest, positively affecting their comprehension of Indonesian language materials. Factors influencing reading interest included internal factors—such as motivation (a strong desire to read for information, knowledge, or entertainment) and reading skills (the ability to understand and enjoy written texts)—and external factors, including the family environment (parental support in providing books, encouraging reading, and creating a supportive atmosphere) and the school environment (the teacher’s role in teaching reading skills and organizing engaging reading activities). However, certain conditions within these factors could also lead to a decline in students’ reading interest.